Fatigue behavior and surface characterization of a Y-TZP after laboratory grinding and regeneration firing. (December 2018) - Polli, Gabriela Scatimburgo; Hatanaka, Gabriel Rodrigues; Abi-Rached, Filipe de Oliveira; Góes, Márcio de Sousa; Reis, José Mauricio dos Santos Nunes
Abstract: This study evaluated the effect of grinding and regeneration firing on the flexural fatigue limit and surface characterization of Lava™ Y-TZP ceramic. Forty bar-shaped specimens with 20 × 4.0 × 1.2 mm constituted the as-sintered group ( AS = control group), and 80 specimens with 20 × 4.0 × 1.5 mm were ground with cylindrical laboratory stone under water-cooling ( WG ) or in a dry condition ( G ) to reach 1.2 mm in thickness. Half of specimens were submitted to regeneration firing (1000 °C, 30 min), forming the groups AS/R, WG/R and G/R . Fatigue limit (500, 000 cycles, 10 Hz) was determined by staircase method in a 4-point flexural fixture. Data were analyzed by 2-way ANOVA and Tukey HSD tests (α = 0.05). The surface topography (n = 3) and fracture area (n = 3) were evaluated by SEM. Samples were also analyzed by Rietveld refinement from X-ray diffraction data. ANOVA revealed significant differences (P < .001) for grinding protocol, regeneration firing and their interaction. In the groups not submitted to regeneration firing, the mean flexural fatigue limit of WG was higher (P < .05) than that of G and AS, with no statistical difference between each other (P > .05). After regeneration firing the inequality WG > AS > G (P < .05) was observed. The regeneration firing increased the fatigue limit of AS group and decreased those of G and WG groups (P < .05). Grinding protocols created evident grooves on zirconia surface. Failures initiated on tensile side of all specimens. The percentages (wt%) of monoclinic phase before cyclic loading were: AS (7.4), AS/R (6.5), G (2.8), G/R (0.0), WG (4.4), WG/R (0.0); and after cyclic loading: AS (8.6), AS/R (1.2), G (2.4), G/R (5.7), WG (6.3), WG/R (0.0). Wet grinding did not compromise the fatigue limit of zirconia, increasing its mechanical strength. Regeneration firing reduced the fatigue limit of ground samples, despite reducing the amount of monoclinic phase in all experimental conditions. Highlights: Low speed grinding with diamond stone did not compromise the fatigue limit of Y-TZP. Regenerative firing may detrimentally affect the mechanical strength of Y-TZP. Y-TZP surface topography is significantly altered after ground with diamond stone.